2023
DOI: 10.1007/s40789-023-00584-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cooling rate on mechanical properties and failure mechanism of sandstone under thermal–mechanical coupling effect

Abstract: High geo-temperature is one of the inevitable geological disasters in deep engineering such as resource extraction, space development, and energy utilization. One of the key issues is to understand the mechanical properties and failure mechanism of high-temperature rock disturbed by low-temperature airflow after excavation. Therefore, the experimental and numerical investigation were carried out to study the impact of cooling rate on mechanical properties and failure mechanism of high temperature sandstone. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Compared with granite and shale, sandstone is less sensitive to LN 2 cooling. Guo et al [36] also observed that with an increase in cooling rate, the degree of rock fragmentation increases, and the number of microcracks increases exponentially.…”
Section: Introductionmentioning
confidence: 95%
“…Compared with granite and shale, sandstone is less sensitive to LN 2 cooling. Guo et al [36] also observed that with an increase in cooling rate, the degree of rock fragmentation increases, and the number of microcracks increases exponentially.…”
Section: Introductionmentioning
confidence: 95%